Zeal, Agility and Benefaction in Cross Border Delivery: An African Perspective - Baijnath, Narend (South African Journal of Higher Education, 2016)
Internationalization and cross border higher education have received much attention in recent scholarship on the subject but the perspectives are largely those of the developed world. Internationalization and cross border delivery have distinct meanings for and are experienced differently by African scholars and administrators in African universities. The most important of these differences will be addressed in the article through an examination, in particular, of the impetus behind the rapid increase in cross border delivery on the African continent, a brief indication of how various institutions are faring, and the potential impact of cross-border delivery on higher education on the continent. The focus however, will be on Internationalization and social justice for it is these latter concepts that are most cogently expressed in South African and African higher education debates at the present time. The University of South Africa is used as a reference point with the focus on the particularities of a university that has taken as its starting point a zealous commitment to service and development in its internationalization and cross border education efforts on the African continent.